Efforts to Improve the Understanding of Darun Nasya Junior High School Students on Static Electricity Materials by Using the Inquiry-Based Learning Learning Model - Novita, Indri; Alfaris, Muhammad; Zahroh, Nabilah Sulaimah; Nurul Azmi, Rd. Sri Haifah; Sanjaya, Syam Syam (Annpublisher, 2025)
Education has an important role in improving students' understanding of scientific materials, especially physics. This study identifies the low knowledge of junior high school grade IX students regarding the concept of static electricity, and this research aims to improve the understanding of Darun Nasya junior high school students towards static electricity materials through the application of Inquiry-Based Learning (IBL) learning model. The method used is an experiment with two groups: the experimental group using the IBL model and the control group using conventional learning methods. Data was collected through pre-test and post-test tests and by observing student activities. The results showed a significant improvement in the understanding of the concept of static electricity in the experimental group. The average post-test score of the experimental group increased from 50% to 80%, while the control group only experienced a marginal increase. This shows that the Inquiry-Based Learning model can improve students' understanding of static electricity materials. This study suggests applying the IBL model as a more effective learning alternative to understanding junior high school physics material.